Surface-initiated polymerization on laser-patterned templates morphological scaling of nanoconfined polymer brushes - Mathieu, Mareike (Langmuir : the ACS journal of surfaces and colloids, 2009)
Nonlinear laser processing of silane-based monolayers is used to fabricate nanostructured chemical templates for the selective growth of polymer brushes in confined domains via surface-initiated polymerization (SIP). Upon varying the laser parameters, reactive domains with lateral dimensions from several micrometers down to the sub-100-nm range are fabricated. This provides a versatile means for studying the morphological scaling behavior of confined polymer brushes. Here, the surface-initiated growth of a stimuli-responsive polymer, poly(N-isopropylacrylamide) (PNiPAAm), via atom transfer radical polymerization (ATRP) is investigated. Polymer chains at the domain boundaries extend into the surrounding polymer-free areas. For this reason the width of confined polymer brushes is significantly larger than that of the underlying domains. Within experimental error, though, the excess width does not depend on the domain size. In contrast, the brush height decreases more and more when the domain size falls below a certain value. Simple considerations point to a geometrical scaling relation between height and width of the polymer brushes. These results are considered as essential for implementation of SIP routines in laser-assisted fabrication schemes targeting micro- and nanofluidic applications